Prinsip Pembelajaran Bahasa Arab Daring Perspektif Rusydi Ahmad Thu'aimah - Al-Mubassyir, Muhammad (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
The Covid-19 has been encouraging the educational sector to reconstruct its systems and implementation, including in Arabic language education. Among the alternative Arabic learning systems that comply with health protocols and have been implemented by many educational institutions is online learning. However, this alternative learning system still requires a deeper review of the learning principles. By using a descriptive qualitative method based on library research, this article reveals the basic principles of online Arabic learning from the perspective of Rusydi Ahmad Thu'aimah. Data is processed from Thu'aimah's works using integrated reading techniques linked to online learning facts from various articles and news sources. This article produces three aspects of online Arabic learning principles from Thu'aimah's perspective: communication principles, learning method principles and learning media principles. So far, no Thu'aimah learning theories have connected them to online learning. These findings can be the primary for implementing of online Arabic learning system today and in the future, both during a pandemic and post-pandemic.